ANALISIS KOMPENSASI FINANSIAL DAN STRES KERJA TERHADAP KINERJA DRIVER MAXIM BENGKULU DALAM MEMENUHI KEBUTUHAN HIDUP - Muhammad Firza Fernanda; Verdi Mardiansyah; Razi Dharmawan Putra; Dr. Desi Isnaini, MA; Adi Setiawan, Lc., M.E.I5 (Bajang Institute, 2022)
This study aims to analyze the effect of financial compensation and work stress on the performance of maxim drivers in meeting the needs of life. This study uses quantitative methods, the samples in this study were 50 Bengkulu maxim drivers. The analytical technique used in this research is validity test, reliability test, classical assumption test, auto correlation test, and hypothesis testing using t test, f test and coefficient of determination. The results show that financial compensation partially has a positive and significant effect on driver performance. maxim bengkulu in meeting the needs of life. Job stress partially has a positive and significant effect on the performance of the Bengkulu maxim driver in meeting the needs of life. Meanwhile, simultaneously based on the results of the F statistical test, the independent variables of financial compensation and work stress together have a positive and significant effect on the dependent variable of the performance of the Bengkulu maxim driver in meeting the needs of life. The predictive ability of these two variables on the performance of the Bengkulu maxim driver in meeting the needs of life is 49.9%, while the remaining 50.1% is influenced by other variables outside the regression model